The assisting hand assessment for children and youth with brachial plexus birth injury: a study of validity and item hierarchy of AHA-Plex - Marie Holmefur; Ann-Kristin Gunnes Elvrum; Lena Krumlinde-Sundholm (Medical Journals Sweden, 2023)
Objective: Functional assessments that focus on activity performance and that produce valid outcome measures for people with brachial plexus birth injury are lacking. The primary aim of this study was to re-evaluate the internal scale validity of the Assisting Hand Assessment specifically for children and adolescents with brachial plexus birth injury. Two further aims were investigating whether the scale could be shortened for this group while maintaining psychometric quality, and exploring and presenting its item difficulty hierarchy. Design: A cross-sectional psychometric study. Subjects: A convenience sample of 105 children and adolescents (aged 18 months to 18 years, mean 6 years, 7 months, standard deviation (SD) 4 years, 4 months) from Sweden, Norway, and the Netherlands with brachial plexus birth injury. Methods: Participants were assessed with the Assisting Hand Assessment. Data were analysed with Rasch measurement analysis. Results: The 20 Assisting Hand Assessment items together measured a unidimensional construct with high reliability (0.97) and the 4-level rating scale functioned well. Item reduction resulted in 15 items with good item fit, unidimensionality, reliability and acceptable targeting. Conclusion: Assisting Hand Assessment for people with brachial plexus birth injury, called AHA-Plex, has 15 items and good internal scale validity. A unique item hierarchy for people with brachial plexus birth injury is presented.